2001
DOI: 10.2165/00019053-200119110-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis and the Consistency of Decision Making

Abstract: The results of this preliminary study indicate that decisions to recommend a drug for listing by the PBAC in the last few years have, by and large, been consistent with the notion of economic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(110 citation statements)
references
References 14 publications
2
107
0
1
Order By: Relevance
“…All three strategies had an ICER under $50,000 per LYG, which is regarded as the upper limit of acceptable cost-effectiveness in the Australian health system [24,31]. An incremental cost of AU$12,405 per LYG, meant colonoscopy screening every five-year appears to be the most cost effective strategy of the three tested.…”
Section: Discussionmentioning
confidence: 99%
“…All three strategies had an ICER under $50,000 per LYG, which is regarded as the upper limit of acceptable cost-effectiveness in the Australian health system [24,31]. An incremental cost of AU$12,405 per LYG, meant colonoscopy screening every five-year appears to be the most cost effective strategy of the three tested.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the CEA thresholds advocated by Laupacis et al [3], suggest that health-care programmes, which cost less than US$12 800 (CAN$20 000) per QALY are highly cost effective, but weak if the ratio exceeds US$64 000 (CAN$100 000). A study by George et al [4] suggests that these thresholds are more in line with what is deemed appropriate by decision makers. George et al looked at the past decisions of the Australian Pharmaceutical Benefits Advisory Committee and found that the committee was unlikely to recommend a drug for listing if the additional cost per life year gained exceeded US$40 400 (AU$76 000).…”
Section: Introductionmentioning
confidence: 94%
“…Willingness to pay (WTP) thresholds for funding of new interventions are primarily published in terms of cost per QALY (with limited WTP thresholds based on life years gained) and so use of cost-utility analysis would enable researchers to compare their study findings against generally accepted WTP thresholds (Kaplan & Bush 1982, George et al . 2001, Simoens 2009, Shiroiwa et al . 2010).…”
Section: Discussionmentioning
confidence: 99%